Sovereign Debt and Supersanctions in Emerging Markets: Evidence from Four Southeast European Countries, 1878-1913 - Andreea-Alexandra Maerean; Maja Pedersen; Paul Sharp (European Historical Economics Society (EHES), 2021)
Do emerging markets need to sacrifice economic sovereignty in order to borrow more cheaply on the international capital markets? To explore this, we exploit a natural experiment following the Treaty of Berlin in 1878 when four Balkan states - Bulgaria, Greece, Romania, and Serbia - received full or de facto independence. Using a novel dataset of monthly bond prices from the Berlin and London stock exchanges, we find that a sacrifice of national sovereignty or 'supersanctions' was one way for these emerging markets to receive more favourable borrowing conditions. Romania never submitted to such measures, however, but was usually able to borrow more cheaply than her neighbours.
Keywords: E4; E5; G1; N2; 330; Bulgaria; creditworthiness; emerging markets; Greece; Romania; Serbia; sovereign debt